Pullout and oblique pullout resistance of enlarged base piles in geogrid reinforced sand - K. V. S. B. Raju; V. Lakshmi (International Journal of Geo-Engineering)
Abstract In the present investigation an attempt is made to study the axial and oblique pullout capacity of monopile and belled pile embedded in geogrid reinforced sand beds by conducting tests on model piles. A model tank of size 1.2mX0.75mX1.5 m is used to study the behaviour of an aluminium model pile under axial and oblique pull-out loads in geogrid reinforced sand bed of relative density 30%. A comparative study was made between monopile and belled piles by varying parameters such as embedment ratios (L/Ds) of 5, 7.5, and 10 respectively and diameter ratios (Db/Ds) of 1.5 & 2 with bell angles of 30°, 45°, and 60° under axial and oblique inclination angle of 30˚& 45˚.The use of the optimum size of the geogrid reinforcement placed at the bottom of the short pile and at a spacing of 4.5Ds from top in case of intermediate and long pile significantly enhanced the pullout and oblique pullout capacities of both monopile and belled piles. In the case of a monopile, the pull-out capacity increases with an increase in the load inclination angle from 0˚ to 45°, whereas in the case of the belled pile, the pullout capacity decreased with an increase in the load inclination angle. A non-dimensional parameter called the Uplift Improvement Ratio was evaluated, and the results revealed that the efficiency of the geogrid reinforcement was independent of the load inclination, bell angle, Db/Ds ratio, and L/Ds ratio when the optimum size of the geogrid was placed at optimum position of the belled pile foundation. It was also found that the obtained breakout factor increases with an increase in the L/Ds ratio and load inclination angle but the influence of the bell angle on the breakout factor was found to be marginal.The obtained values of the breakout factor were compared with the existing limit equilibrium theory, and it was found that the results of the breakout factor were in good agreement with the Meyerhof and Adam theory for both unreinforced and geogrid-reinforced sand beds.